ANALYSIS OF FACTORS AFFECTING THE WORKING HOURS OF FEMALE TRADERS IN KUMBASARI MARKET - Ni Kadek Deby Davina Cahya Putri; Ni Made Tisnawati (INTERNATIONAL JOURNAL OF ECONOMIC LITERATURE, 2025)
The participation and involvement of all segments of Indonesian society, regardless of social group, are essential for the smooth implementation of national development. Over time, married women are no longer confined to the role of housewives but have also begun contributing to household income by entering the labor market. This study aims to: (1) analyze the simultaneous effect of age, marital status, number of dependents, and non-labor income on the working hours of female traders at Kumbasari Market, Denpasar City; and (2) analyze the partial effect of these variables on their working hours. The study involved a population of 341 traders, from which 77 respondents were selected using a non-probability sampling technique with an accidental sampling method. Data were analyzed using descriptive analysis and a semi-log non-linear regression model. The findings reveal that: (1) age, marital status, number of dependents, and non-labor income simultaneously influence the working hours of female traders; (2) age and non-labor income have a negative partial effect; (3) the number of dependents has a positive partial effect; and (4) married female traders tend to work fewer hours on average compared to those who are unmarried. Based on these results, it is recommended that female traders pay more attention to their health by adopting a healthy lifestyle, managing rest time proportionally, and utilizing free health check-up facilities.